1996
DOI: 10.1042/bj3170313
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic analysis of the mitochondrial quinol-oxidizing enzymes during development of thermogenesis in Arum maculatum L

Abstract: The dependence of the rate of oxygen uptake upon the ubiquinone (Q)-pool reduction level in mitochondria isolated during the development of thermogenesis of Arum maculatum spadices has been investigated. At the alpha-stage of development, the respiratory rate was linearly dependent upon the reduction level of the Q-pool (Qr) both under state-3 and -4 conditions. Progression through the beta/gamma to the delta-stage resulted in a non-linear dependence of the state-4 rate on Qr. In the delta-stage of development… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
2

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 35 publications
3
22
2
Order By: Relevance
“…4 indicate that the alternative oxidase is expressed in a functional form, indicating that following import and processing the protein is correctly folded and importantly, the necessary enzymes for the incorporation of iron are present in S. pombe. Furthermore such observations indicate the expression of a single polypeptide is sufficient for enzyme activity, which is in contrast to that observed in thermogenic tissues (39,40) and soybean (4,41).…”
Section: Discussioncontrasting
confidence: 49%
“…4 indicate that the alternative oxidase is expressed in a functional form, indicating that following import and processing the protein is correctly folded and importantly, the necessary enzymes for the incorporation of iron are present in S. pombe. Furthermore such observations indicate the expression of a single polypeptide is sufficient for enzyme activity, which is in contrast to that observed in thermogenic tissues (39,40) and soybean (4,41).…”
Section: Discussioncontrasting
confidence: 49%
“…Regarding region 4, which is located at the C terminus of the AOX protein, it has been shown that mutation of a Gly residue close to this region results in an AOX protein with an apparent decreased sensitivity to the salicylhydroxamic acid (Berthold, 1998). AOX has previously been successfully purified from A. maculatum thermogenic appendices (Affourtit and Moore, 2004), and such preparations show both pyruvate-sensitive and -insensitive activities (Leach et al, 1996).…”
mentioning
confidence: 99%
“…Mitochondria isolated from this tissue provide a suitable example of a branched plant electron transfer chain in that external NADH is oxidised at a high rate (8) and AOX is engaged in the overall respiration to a considerable degree (9). We report that in this this system, MAQ does not act as an uncoupler but rather as an universal inhibitor of those respiratory enzymes that react with ubiquinone (Q).…”
Section: Introductionmentioning
confidence: 99%
“…maculatum spadices were collected from plants that were approximately at the b /c stage of thermogenesis (10) and growing in local Sussex woods. After collection, the mitochondria were immediately isolated and puri ed as previously described (9). Mitochondria were either used in experiments on the day of isolation or frozen at ¡ 18 ± C with subsequent storage at ¡ 70 ± C for use at a later date.…”
Section: Resourcesmentioning
confidence: 99%